O escândalo da falência da Companhia Geral do Crédito Predial Português na agonia da Monarquia Constitucional (1910) - Oliveira, João (2019)
The goal of this article is to study the journalistic coverage of a bank's insolvency in 1910: the company Crédito Predial Português. We intend to evaluate how the press of the time - particularly, those positioned against the Government and/or the political regime: O Século, O Dia and O Mundo- covered this scandal. Using quantitative and the qualitative methods, we will assess the framing of the news stories, and the tone and language used. We also want to study the role that sources played in the news: how frequent their use, the prevailing categories of confidentiality (from the modern theories' perspective), the amount of information attributed to them, and their socio-professional origins. Through this method, we expect to contribute to a deeper knowledge of the Portuguese press of the first decade of the 20th century, as well as of the journalistic coverage of economic themes.